A Preliminary Investigation on Partial Rootzone Drying (PRD) Effects on Grapevine Performance, Nitrogen Assimilation and Berry Composition - du Toit, P.G.; Dry, P.R.; Loveys, B.R. (South African Journal of Enology and Viticulture, 2017)
Partial rootzone drying (PRD) is an irrigation management technique designed to reduce water use in grapevines without a decline in yield, thereby increasing water use efficiency (WUE). Experiments consisted of field-grown Cabernet Sauvignon, where the PRD grapevines were irrigated with half the amount of water as control grapevines, and Shiraz, where the PRD grapevines received the same amount of water as control grapevines. PRD treatments showed no significant differences in yield or berry composition at harvest, except that PRD grapevines that received half the amount of water had significantly smaller berries than control grapevines. Cabernet Sauvignon PRD grapevines receiving half the amount of water as control grapevines showed a 34 % reduction in main shoot growth and up to a 74% reduction in lateral shoot growth. Shoot growth was inhibited to a lesser extent in Shiraz PRD grapevines receiving the same amount of water, with a 20% reduction in main shoot.growth and a 33% reduction in lateral shoot growth. PRD also significantly reduced stomatal conductance in Cabernet Sauvignon on average by 31 % and 16% in Shiraz. Nitrate reductase (NR) activity in grapevine leaves was significantly lowered in response to PRD, irrespective of the amount of water applied. The reduction in NR activity was closely correlated with the development of the PRD cycle and the associated reduction in stomatal conductance.